2020
DOI: 10.21203/rs.3.rs-18073/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seroprevalence of the hepatitis E virus among blood donors in the Qassim Region, Saudi Arabia

Abstract: Objectives The aim of this study was to evaluate the seroprevalence of hepatitis E virus (HEV), a major public health issue worldwide with the potential for transmission via blood transfusion, in blood donors in the Qassim Region, Saudi Arabia. Serum samples (n = 1,078) were collected from volunteer blood donors from January to April 2019 and tested for the presence of anti-HEV IgG and IgM by indirect enzyme-linked immunosorbent assays. Results Overall, the seroprevalence of anti-HEV IgG and IgM among blood do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Two studies have previously reported the detection of anti-HEV IgM antibodies without the confirmation of a current HEV infection with RNA detection. 16 , 43 It is worth noting that HEV seroprevalence in countries of the expatriate who are involved in our study is also moderate, such as Philippines (11.8%), Sudan (26%), and Egypt (25%). 21 , 25 , 26…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Two studies have previously reported the detection of anti-HEV IgM antibodies without the confirmation of a current HEV infection with RNA detection. 16 , 43 It is worth noting that HEV seroprevalence in countries of the expatriate who are involved in our study is also moderate, such as Philippines (11.8%), Sudan (26%), and Egypt (25%). 21 , 25 , 26…”
Section: Discussionmentioning
confidence: 76%
“…66 This is lower than the previously reported HEV IgG seroprevalence before 2013, where it ranged between 14% and 18% from the southern and western regions, respectively. 16 , 42 , 43 , 67 This could indicate a reduction in the HEV exposure in the past few years or a regional difference in the country. The western region (Mecca and Jeddah) receives the majority of Saudi Arabia's visitors for religious purposes, who may import a silent infection and increase the exposure of the local population.…”
Section: Discussionmentioning
confidence: 99%